Stoichiometry and kinetic of the aerobic oxidation of phenolic compounds by activated sludge - Lobo, Cintia Cecilia (2013)
The aerobic degradation of phenol (PH), catechol (CA), resorcinol (RE), pyrogallol (PY), and hydroquinone (HY) by phenol-acclimated activated sludge was investigated. A Haldane-type dependence of the respiration rate on PH, RE, and HY was observed; CA and PY exhibited a biphasic respiration pattern. According to the initial biodegradation rate, tested compounds were ordered as follows: CA > PH >> PY RE > HY. Also, they exhibited the following degree of toxicity to their own degradation: PY >> CA RE >> PH > HY. Oxidation coefficients for PH, PY, RE, and HY were constant as a function of the consecutive additions of the compound. Conversely, an increase of YO/S from 1 to 1.5 molO2 molCA1 was observed during repeated additions of CA. The role of some enzymes involved in the aerobic degradation pathways of the tested compounds is discussed and related to the obtained results